Current-Carrying Wear Behavior of Cu–TiC Coatings Obtained Through High-Speed Laser Cladding on Conductive Slip Rings of 7075 Aluminum Alloy - Shiya Cheng; Yuankai Zhou; Xue Zuo (Metals)
Cu-5wt%TiC coatings were fabricated by high-speed laser cladding on the 7075 aluminum alloy substrate using various scanning speeds to improve its current-carrying wear resistance. The effects of scanning speed on the microstructure, phase, hardness, and current-carrying tribological properties of the coating were investigated using a scanning electron microscope, an X-ray diffractometer, a hardness tester, and a wear tester, respectively. The results show that the increase in scanning speed accelerates the coating’s solidification rate. Among the samples, the coating comprised of equiaxed crystals prepared at 149.7 mm/s presents the best quality, but solidification speeds that are too rapid lead to elemental segregation. The hardness of the coating also decreases with the increase in scanning speed. The coating prepared at 149.7 mm/s exhibits the best wear resistance and electrical conductivity. The wear rate of the coating prepared at 149.7 mm/s at 25 A was 4 × 10−3 mg·m−1, respectively. During the current-carrying friction process, the presence of thermal effects and arc erosion cause the worn track to be prone to oxidation, adhesion, and plastic deformation, so the current-carrying wear mechanisms of coatings at 25 A include adhesive wear, oxidation wear, and electrical damage.